Purification, kinetic characterization of thermostable multicopper oxidase from the oyster mushroom and its versatility for greener agro-pulp bio bleaching in the paper industry: Purification and characterization of laccase from P. florida - Kaur, Manmeet; Shivani Sharma; Inderpal Kaur; Harpreet Singh Sodhi; Ravish Choudhary; Sezai Ercisli; Hafize Fidan; Dasci, Elanur; Riaz Ullah; Ahmed Bari (Cellular and Molecular Biology, 2024)
Production of a thermostable laccase from Pleurotus florida was reported for the first time, both in submerged and solid-state fermentation using agro-industrial residues. This enzyme was purified using ammonium sulphate precipitation (60-90%), Sephadex G-100 and DEAE column ion exchange chromatography, respectively. The laccase was purified to 21.49 fold with an apparent molecular weight of 66 kDa and had an optimal pH of 5 with temperature stability at 60°C. Metal ions such as Cu2+ (91.26 µmole/mL/min), Mg2+ (68.15 µmole/mL/min), and Fe2+ (1.73 µmole/mL/min) enhanced the laccase activity, but Fe2+ (1.73µmole/mL/min) inhibited the enzyme activity. The purified laccase had Km and Vmax of 16.68 mM and 26.73 µmole/mL/min for guaiacol as a substrate. The isolated enzyme was characterized by FT-IR which revealed bands at 3655.0 cm-1, 2894.7 cm-1, and 1151.7 cm-1 corresponding to primary amines, C-H stretch, and amide –III, respectively. The enzymatic bio bleaching of paddy straw pulp was found to be most effective which resulted in a lowering of kappa number and yellowness by 19.47% & 17.84% whereas an increase in brightness and whiteness by 41.92%. & -19.61%. Thus, this might be stated that the crude laccase from P. florida can be exploited to reduce the toxic waste load for managing environmental pollution and helps in enhancing the yield and quality of the paper.